Directory of clinical databases: improving and promoting their use. Issue 5 (7th October 2003) - Black, N; Payne, M
Abstract : Background: The controversy surrounding the actual and potential use of clinical databases partly reflects the huge variation in their content and quality. In addition, use of existing clinical databases is severely limited by a lack of knowledge of their availability. Objectives: To develop and test a standardised method for assessing the quality (completeness and accuracy) of clinical databases and to establish a web based directory of databases in the UK. Methods: An expert group was set up (1) to establish the criteria for inclusion of databases; (2) to develop a quality assessment instrument with high content validity, based on epidemiological theory; (3) to test empirically, modify, and retest the acceptability to database custodians, face validity and floor/ceiling effects; and (4) to design a website. Results: Criteria for inclusion of databases were the provision of individual level data; inclusion in the database defined by a common circumstance (e.g. condition, treatment), an administrative arrangement, or an adverse outcome; and inclusion of data from more than one provider. A quality assessment instrument consisting of 10 items (four on coverage, six on reliability and validity) was developed and shown to have good face and content validity, no floor/ceiling effects, and to be acceptable to database custodians. A website (www.docdat.org ) was developed. Indications over the first 18 months (number of visitors to the site) are that it is increasingly popular. By November 2002 there were around 3500 hits a month. Conclusions: A website now exists where visitors can identify clinical databases in the UK that may be suitable to meet their aims. It is planned both to develop a local version for use within a hospital and to encourage similar national systems in other countries.